ROLE OF THYROID DYSFUNCTION IN INFERTILE WOMEN WITH MENSTRUAL DISTURBANCES - Rabia Syed; Neelam Abbas; Amna Najam; Misbah Harim; Beenish Riaz (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Infertility is one of the medial, social and psychological burdens in this part of world. Thyroid dysfunction can lead to menstrual disturbance, anovulatory cycles, and decreased fecundity. Proper management of thyroid dysfunction can result restoration of normal fertility. Therefore it is very important to screen thyroid abnormalities among women with infertility. Objective: To assess the role of thyroid dysfunction in infertile women with menstrual disturbances Methodology: This cross-sectional study was conducted at the Department of obstetrics and gynaecology Allama Iqbal Teaching Hospital Dera ghazi khan. The study duration was one year from March 2023 to March 2024. A total of 200 in- fertile women were enrolled. Their clinical detail along with menstrual history was recorded on a predesigned proforma. Estimation of serum levels of thyroid hormones (TSH, T3 and T4) were performed on Chemiluminescence Immuno- assay Analyzer CLIA-IIS. Statistical analysis was performed using the statistical package for social sciences (SPSS) version 24. Results: Amongst 200 infertile women 130 (65%) were cases of primary infertility and 70 (35%) of secondary infertility. The mean age of primary infertile women was 28.12 (±5.99) years and secondary infertile women 29.11 (±2.24) years. Irregular menstrual cycles were found in 12 out of 40 hyperthyroid, 3 out of 5 hypothyroid and 27 out of 155 euthyroid infertile women. A significant association was observed on comparison of thyroid profile with irregularities in menstrual cycle (p=0.002). Conclusion: Our study concludes that thyroid dysfunction plays a significant role in female infertility which may manifest as menstrual disturbances especially in primary infertile women. Thyroid profile can help us in prompt diagnosis and timely initiation of therapy. Therefore thyroid hormone profile must be included in the routine workup of infertile women in our setup.